Public Health Efforts and the Decline in Urban Mortality: Reply to Cutler and Miller - D. Mark Anderson; Kerwin Kofi Charles; Daniel I. Rees (Institute of Labor Economics (IZA), 2019)
This is a rejoinder to a comment written by Cutler and Miller on our recent paper, "Public Health Efforts and the Decline in Urban Mortality" (IZA DP No. 11773), which reanalyzes data used by Cutler and Miller to investigate the determinants of the urban mortality decline from 1900 to 1936. Two main results emerge from our reanalysis of their data: (1) correcting infant mortality counts reduces the estimated effect of filtration on infant mortality by two-thirds, from -43 log points to -13 log points; and (2) using a consistent method of the calculating the total mortality rate shrinks the estimated effect of filtration on total mortality by half, from -16 log points to -8 log points. In this rejoinder, we argue that the much-reduced estimate of the effect of water filtration on infant mortality is a dramatic and surprising departure from the consensus view in the literature. In addition, we show that the estimated effect of water filtration on total mortality is extremely fragile. Evidence of this fragility may also be found in recent work by Catillon, Cutler and Getzen (2018).
Keywords: I15; I18; 330; public health; mortality; chlorination; filtration; pasteurization; sewage